2015
DOI: 10.4269/ajtmh.14-0612
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Insecticide Allocation Strategies Based on Houses and Livestock Shelters for Visceral Leishmaniasis Control in Bihar, India

Abstract: Abstract. Visceral leishmaniasis (VL) is the most deadly form of the leishmaniasis family of diseases, which affects numerous developing countries. The Indian state of Bihar has the highest prevalence and mortality rate of VL in the world. Insecticide spraying is believed to be an effective vector control program for controlling the spread of VL in Bihar; however, it is expensive and less effective if not implemented systematically. This study develops and analyzes a novel optimization model for VL control in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Proper surveillance is crucial for controlling leishmaniasis in endemic countries; however, there is a need to develop methods that can measure disease transmission rates effectively using existing limited data [ 29 ] and can be used to evaluate control programs [ 40 ]. Leishmaniasis-affected regions are primarily resource-constrained and hence face various challenges to gathering regular comprehensive data.…”
Section: Discussionmentioning
confidence: 99%
“…Proper surveillance is crucial for controlling leishmaniasis in endemic countries; however, there is a need to develop methods that can measure disease transmission rates effectively using existing limited data [ 29 ] and can be used to evaluate control programs [ 40 ]. Leishmaniasis-affected regions are primarily resource-constrained and hence face various challenges to gathering regular comprehensive data.…”
Section: Discussionmentioning
confidence: 99%
“…Understandably, proper use of bed-nets have been found to have a protective effect on people across several studies, and sleeping on a cot (versus on the floor) also demonstrated a protective effect as well [21, 23, 24, 26–28]. Proximity to domesticated animals is found to play a complex role in containing, spreading and serving as a possible reservoir of the parasite [32]. For example, some studies found that proximity to livestock provided a protective effect against leishmaniasis as livestock get bitten more instead of humans [24, 25], whereas in Uttar Pradesh, India, the risk of leishmaniasis was found to increase with increased numbers of cattle in the vicinity of a household because of large number of sandflies were attracted to cattle sites than to other livestock sites [23].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, models can be used to design control strategies, via analysing a critical threshold quantity, model's basic reproduction number (R 0 ), interpreted as the average number of secondary cases of infection as a result of the introduction of a primary infection into a completely susceptible population [31][32][33]. For example, Gorahava et al [34] developed an optimization model for anthroponotic visceral leishmaniasis control in India and used it to identify an optimal allocation strategy of choosing and distributing insecticide based on the number of human and cattle populations in each district of the affected region. Studies have also shown that the culling of seropositive dogs, the use of insecticide-impregnated dog collars, and the vaccination of dogs significantly contribute to reducing the prevalence of zoonotic visceral leishmaniasis infection in both canines and humans [35,36].…”
Section: Studies On Modelling Dynamics Of Leishmaniasismentioning
confidence: 99%